Production of bacterial nanobiocomposites of polyhydroxyalkanoates derived from waste and bacterial nanocellulose by the electrospinning enabling melt compounding method. Issue 2 (11th June 2015) - Martínez‐Sanz, Marta; Lopez‐Rubio, Amparo; Villano, Marianna; Oliveira, Catarina S. S.; Majone, Mauro; Reis, Maria; Lagarón, Jose M.; Lagarón, José M.; López‐Rubio, Amparo; Fabra, María José
ABSTRACT This work reports on the characterization of nanocomposites fully synthesized by bacteria, consisting of polyhydroxybutyrate‐co‐hydroxyvalerate (PHBV) matrices reinforced with bacterial cellulose nanowhiskers (BCNW). Two PHBV grades, with 9% HV (PHBV9) and 16% HV (PHBV16), were synthesized using food industry waste feedstocks and compared with a 3% HV commercial grade (PHBV3). Whereas PHBV3 presented a high barrier performance but excessive brittleness, PHBV9 and PHBV16 showed a more ductile behavior and reduced barrier properties. Subsequently, BCNW were incorporated into the PHBVs by a high‐throughput electrospinning technique to produce master‐batch formulations with relatively high nanofiller concentrations. The hybrid ultrathin fibers showed homogeneous morphologies and greater thermal stability than the pure PHBV fibers. Nanocomposites were then produced by melt mixing PHBVs with the hybrid fibers. Despite the low compatibility between the extremely hydrophilic BCNW and the hydrophobic PHBVs, the nanofiller was highly dispersed and provided a reduction in oxygen permeability of the PHBV3 matrix without relevant modifications in mechanical performance. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42486.